Moss transplantats’ morphological changes as a reaction on air pollution in industrial region (CHORNOMORSKI BOTANICAL JOURNAL, 2008)
Typical morphological changes of epiphytic moss transplantats under the impact of environmental pollution in the city of Makeyevka (Donetsk region) are determined. It is found that the degree of morphological characteristics of such moss species as Orthotrichum pumilum Sw. (=Ortotrichum fallax Bruch.) and Leptodictium riparium (Hedw.) Warnst. positively correlates with the air pollution intensity. These sensitive species can serve the informative indicators of air property in industrial region. Relatively high resistance of moss species Leskea polycarpa Hedw. in the conditions of intensive air pollution is confirmed. The degree of anthropogenic pressure in three zones of Makeyevka (Donetsk region) is determined.
Keywords: mosses, transplantation, air pollution.